Saturation Effects in 3p3L Power Transformers due to Geomagnetically Induced Currents - Kerr, Evan (Department of Electrical Engineering, 2024)
Geomagnetically induced currents (GIC's) caused by solar storms or other sources of dc excitation can impact the normal operation of power transformers in transmission networks. The impact is caused by the dc current introduced into the windings of a transformer energised with ac, which leads to a simultaneous dc magnetomotive force (mmf) resulting in part-cycle saturation of the core and so, heat related ageing and failures. A generally accepted theory on the impact of GIC's on transmission networks is that three-phase three-limb (3p3L) power transformers are not affected by this phenomenon. The basis is that a three-limb core forms balanced return paths which oppose the dc flux evenly in each limb, thereby neutralising the effect. The challenge is this theory only remains true if the circuit resistance of the three-phase lines connected to the transformer are balanced, which has proven difficult to achieve in practice. This study set up laboratory experiments to evaluate the effect of simultaneous ac and dc in the windings of an unloaded 3p3L transformer while simulating realistic unbalanced conditions. To ensure a valid test protocol, the transformer was designed as a scaled-down model of a power transformer with a core constructed using four step-lap mitred joints and a high quality electrical steel. This was to closely resemble the performance of a normal power transformer. The source supply for the test circuit was carefully designed and tested to ensure that it was sufficiently robust that it would not affect the results of the transformer under test (TuT). The initial testing was of symmetrical ac conditions to establish a performance benchmark at normal operation and the TuT nameplate rating, and to emulate core saturated conditions by over-exiting the core for exploratory core stray flux recordings. The dc testing that followed required adjustable levels of dc current and the unbalance to emulate a range of GIC conditions. At each setting of dc and unbalance, the excitation parameters such as THD were recorded using a power analyser. Simultaneously, the core stray flux was recorded using search coils, while tank ‘hot-spot' temperatures from stray flux eddy current heating were recorded. Finally, the audio levels of the 3p3L transformer in balanced and unbalanced GIC conditions were analysed. The results of the tests challenge the assumption that 3p3L power transformers are immune to GIC primarily because it is not possible to ensure ideally balanced conditions in the field. The importance of the transformer core design was highlighted by showing its significant contribution to the GIC vulnerability. The core joints of a four step-lap core was shown to saturate before the bulk core areas that emphasised the need for continual careful attention to core design and construction in an effort to reduce inherent design vulnerabilities.